PERBEDAAN INFORMASI ANATOMI CITRA CT-SCAN SINUS PARANASAL POTONGAN CORONAL DENGAN VARIASI REFORMAT SLICE THICKNESS PADA KASUS RINOSINUSITIS KRONIS - Safina Yulianarrahma; Bekti Safarini; Nanang Sulaksono (Perhimpunan Radiografer Indonesia (PARI), 2019)
Background : Chronic rhinosinusitis is defined as inflammation of the nose characterized by two or more symptoms, one of which should be either obstruction, facial pain pressure, reduction of smell for more than 12 weeks. Multiplanar reconstruction is a computer program that can create coronal, sagittal, and paraxial images from a stack of contiguous transverse axial scans. There are several parameters that support CT-Scan image quality, one of which is slice thickness. The slice thickness is an incision where the value chosen by the operator is in accordance with clinical requirements. The purpose of this research is to find out difference of image anatomic information in coronal ct scan paranasal sinuses with reformat slice thickness variations in chronic rhinosinusitis and the optimal reformat slice thickness. Method : This type of research is an experimental quantitative that was located in the Radiology Installation of dr. Moewardi Hospital Surakarta on March-May 2019. This research used 8 samples and 3 respondents, where slice thickness coronal was reformatted with variations 1 mm, 1,5 mm, 2 mm, 2,5 mm, and 3 mm. Anatomical criteria assessed were nasal septum deviation, mucosal thickening, and concha bullosa. In this research, Kappa test was conducted to determine the degree of allignment between respondents. Then analyzed by Friedman test to determine difference of image anatomic information in coronal ct scan paranasal sinuses with reformat slice thickness variations in chronic rhinosinusitis and to find out which the optimal reformat slice thickness by looking at the highest mean rank. Result : The results of this research showed a significant difference between the use reformat slice thickness variations to the anatomy criteria with p value < 0,05. Reformat slice thickness 1 mm seems very clear on nasal septum deviation, mucosal thickening, and concha bullosa, 1,5 mm and 2 mm seems very clear on nasal septum deviation and mucosal thickening, 2,5 mm seems very clear on nasal septum deviation, 3 mm seems very clear on nasal septum deviation and concha bullosa. Conclusion : Based on the result that there is a difference of image anatomic information in coronal CT-Scan paranasal sinuses in chronic rhinosinusitis with the most optimal reformat slice thickness is 1 mm.